Primary tracheobronchial necrosis after esophagectomy: A nationwide multicenter retrospective study in Japan. Issue 2 (8th October 2022) - Sakai, Makoto; Saeki, Hiroshi; Sohda, Makoto; Korematsu, Mizuki; Miyata, Hiroshi; Murakami, Daizo; Baba, Yoshifumi; Ishii, Ryo; Okamoto, Hiroshi; Shibata, Tomotaka; Shirabe, Ken; Toh, Yasushi; et al.
Abstract: Background: The clinical features of postoperative primary tracheobronchial necrosis (P‐TBN; the necrosis without anastomotic leakage or other cervical and mediastinal abscess) remains unclear. This nationwide multicenter retrospective study first investigated the clinical features of P‐TBN after esophagectomy for upper aerodigestive tract cancer with a large cohort. Methods: As a study of the Japan Broncho‐Esophagological Society, a nationwide questionnaire survey was conducted in 67 institutions. The clinical data of 6370 patients who underwent esophagectomy for laryngeal, pharyngeal, and esophageal cancer between 2010 and 2019 were collected. Grades of P‐TBN were defined as follows: Grade 1, mucosal necrosis; Grade 2, transmural bronchial wall necrosis without fistula or perforation; Grade 3, transmural bronchial wall necrosis with fistula or perforation. Results: P‐TBN was observed in 48 (0.75%) of 6370 patients. The incidences of P‐TBN for pharyngo‐laryngo‐cervical esophagectomy (PLCE; n = 1650), total pharyngo‐laryngo‐esophagectomy (TPLE; n = 205), and subtotal esophagectomy (SE; n = 4515) were 2.0%, 5.4%, and 0.1%, respectively. The upper mediastinal LN dissection ( P  = 0.016) and the higher level of the tracheal resection ( P  = 0.039) were significantly associated with a higher grade of necrosis in PLCE and TPLE. Overall survival rates were significantly lower in patients with Grade 2 ( P  = 0.009) and Grade 3 ( P  = 0.004) than in those with Grade 1. Conclusion: The incidence of TBN restricted to P‐TBN was lower than previously reported. Maintaining the tracheal blood flow is essential to prevent worsening P‐TBN, especially in PLCE and TPLE. Our new P‐TBN severity grade may predict the outcome of patients with P‐TBN. Abstract : The analyses of 6, 370 patients revealed the incidence of primary tracheobronchial necrosis (P‐TBN) after esophagectomy is 0.75%. TBN severity associated with prognosis of patients with P‐TBN.